Leading The Future Through Student Leadership: A Bibliometric Mapping - Adnan, Nor Syamimi Mohamed; Aziz, Mohd Kasturi Nor Abd; Halim, Jasin Abd; Ridzuan, Ahmad Hifzurrahman; Israr, Mohammad (Interdisciplinary Journal of Social Sciences, 2026)
Student leadership has emerged as a strategic field for developing future-ready graduates; however, its global research landscape remains insufficiently mapped. This study aims to systematically analyze the intellectual structure and geographical distribution of student leadership research from 2000 to 2026. Using a bibliometric approach, data were collected from the Scopus database with keywords such as student leadership, youth leadership, peer leadership, and student leader, resulting in 1,536 publications. Data were refined using OpenRefine, while Scopus analytical tools were employed to generate statistical trends. The findings indicate a significant and consistent growth in publication output, peaking in recent years. The United States dominates the field, followed by Canada and Australia, reflecting the strong influence of Western scholarship. However, emerging contributions from Asia, particularly China and Malaysia, signal a shift toward a more multipolar research landscape. The intellectual development of the field shows a transition from hierarchical leadership models to more relational and socially oriented perspectives. This study provides a comprehensive bibliometric overview that highlights key trends, influential works, and research gaps. The findings offer valuable insights for scholars, educators, and policymakers to promote more inclusive and globally relevant student leadership development